Tipologiâ gazetnyh rečevyh žanrov - Duskaeva, Liliâ R. (Stylistyka, 2021)
The paper deals with the genre typology of the publicistic functional style. The speech genres are interpreted as a three-part system reflecting the interaction of the semantic positions both of the writer and the addressee. For the first time there has been characterized the system of the reader's genre needs which are nom1ally taken into consideration by a reporter when creating the text ofthis or that particular genre. As a result of the study into the problem it has been stated that various informational needs of the audience determine the compositional andthematic genres'peculiarities, as well as the communicative requirements and set the stylistic parametres of the pattems. In the paper there is proposed the solution of the disputable issued in linguistics concerning the primary and secondary genres and are revealed the regularities in the different genres' interractions.